The Origins of Elite Persistence: Evidence from Political Purges in Post-World War II France - Toke Aidt; Jean Lacroix; Pierre-Guillaume Méon (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies a new mechanism that allows political elites from a non-democratic regime to survive a democratic transition: connections. We document this mechanism in the transition from the Vichy regime to democracy in post-World War II France. The parliamentarians who had supported the Vichy regime were purged in a two-stage process where each case was judged twice by two different courts. Using a difference-in-differences strategy, we show that Law graduates, a powerful social group in French politics with strong connections to one of the two courts, had a clearance rate that was 10 percentage points higher than others. This facilitated the persistence of that elite group. A systematic analysis of 17,589 documents from the defendants' dossiers is consistent with the hypothesis that the connections of Law graduates to one of the two courts were a major driver of their ability to avoid the purge. We consider and rule out alternative mechanisms.
Keywords: D73; K40; N44; P48; 330; purges; political transitions; elite persistence; connections